CODESRIA Bulletin Online, No. 5, February 2022 - Ethiopia’s Ethnic Federalism and the African Search for Viable Statehood: Matters Arising - Osaghae, Eghosa E. (CODESRIA Bulletin, 2022)
This is the second in a series of articles that CODESRIA is publishing on the issue of nation-building in Africa based on a reflection on the Ethiopian crisis. The article critically discusses the dynamics of federalism as expressed in the Ethiopian case while also mobilizing experiences from across the continent to bring in a comparative dimension. As indicated in CODESRIA Bulletin Online, No. 4, the Council welcomes intellectual contributions and reflections that advance our understanding on these issues. At the time of its negotiation and adoption in the 1990s, the Ethiopian model of ‘ethnic federation’ presented a breath of fresh air for African states grappling with how to balance the devil of diversity and thedeep blue sea of cohesion and integration. It was even more significant that the Ethiopian journey was taking place at the same time that South Africa was transitioning from apartheid to a democratic state, and the rest of Africa was searching for new paradigms of viable statehood. Ethiopia and South Africa were confronting one of the more fundamental but unresolved issues of statehood in Africa: the equitable accommodation of contesting subnationalist forces that in some cases required the acknowledgement of the right of constituent states to self-determination. The history and circumstances of the transitions in the two countries made the issue even more critical not only for them but also the theory and practice of statehood, national integration and federalism in Africa’s divided societies for which the transitions presented new hopes and opportunities in the long-drawn-out search for workable solutions. Ethiopia has a complex past of ethno-regional domination, rebellions and separatist agitations, which reached a head in the wars of the ethnically based liberation movements (1974–1991), with the centralist and centripetal forces of Ethiopia Tikdem (Ethiopia First) contending with those of regionalism and autonomy. South Africa’s situation was different, if not peculiar, but the circumstances that demanded a political solution were not entirely dissimilar. Like Ethiopia, the opposing forces were those for centralization/national integration and those for regional autonomy/separatism. Students of federalism will readily agree that the balance of forces in both situations demanded a federal solution of the variety that operates on the basis of a federal Constitution that shares power between at least two tiers of government (as opposed to less thorough going variants that do not involve a federal Constitution and government). It was just as well that the two countries adopted the federal solution at the time they did because, as Horowitz (2007) argued, as conflict management instrumentalities, federal solutions tend to be more effective when applied at the right time, that is, before conflicts reach disintegrative and irreconcilable points. But whereas South Africa opted for a form of undivided federalism, which substantially followed centrist conventional wisdom with a heavy dose of Jacobinism and has been relatively stable so far, Ethiopia adopted a form of divided federalism within strumentalities that were unprecedented and unique in Africa, and even in the universe of federal theory and practice, and which has been troubled and unstable. Ethiopia’s ethnic federation not only had the country’s major (ethnic) nations, nationalitiesand peoples (defined as groups witha common culture, language or religion and an identifiable territory) as constituent regional states with substantial autonomous powers, but also granted the nationalities the right to self-determination, including the ‘unconditional right’ to secede. The country’s history of intense agitations for separation and regional autonomy and contested hegemony, which shaped the transition, seemed to demand this kind of divided federalism. However, the underlying contradictions of ethnic federation and statehood raised questions about the feasibility and stability of the arrangement, and whether it was meant to be short-term or long-term, a means to an end, or an end in itself. The structure of the federal system raised even more fundamental questions. How workable is a federal formula that: freezes ethnonationalities as permanently divided entities, thereby reproducing historical and structural inequalities and discriminations, including the domination, oppression and relegation of some groups (especially ethnic and religious minorities), whose political economy deprives constituent units of the resources and capacities to discharge autonomous powers on matters as basic as the development of local languages and mother tongue education, that was constructed by an authoritarian regime and assigns extensive powers of control and intervention to federal authorities over regional states, including most notably the power to declare a state of emergency (which is seen as a legacy of the Derg regime), and holds the ideology of Ethiopia Tikdem overarching and sacrosanct? With regard to (4), the point should be made that, although Ethiopia has a history of insurgency and separatist agitation, dissent has mostly been over equitable accommodation within the state rather than independence from it. (For fairly well-known historical reasons Eritrea was the exception in this regard.) Ethiopia’s experience so far, especially since the political crisis that led to the Oromo and Tigray insurgency and spiralled into civil war under Prime Minister Abiy Ahmed, who acceded to power in 2018, suggests that the ethnic federation may havefailed to meet the expectations of its design and to address the contradictions that underlie the unity and diversity nexus. These contradictions mostly emanate from an endemic African disease, namely, the unrestrained colonial powers of central governments and ruling elites, which undermine the forces of self-government and autonomy and render the core federal principles of non-centralisation, devolution, decentralisation and power-sharing weak and ineffective. In intent and design, Ethiopia’s ethnic federalism appeared capable of curing this disease but, once again, the overbearing power of the centre has proven to be impregnable. The failure of decentralisation schemes to raise the self-governance status of subnational units has been attributed to this factor. In fact, it has been argued that in Ethiopia, like other countries in Africa, decentralisation strengthens the central government rather than subnational governments. So, why has Ethiopia’s ethnic federalism not been able to cure the African disease? To begin with, in spite of the ethno-regional character of regional states and the constitutional efforts to make them the ‘owners’ of the federal government (for example, by having members of the House of Federation, the second national legislative chamber that protects the constituent interests in constitutional interpretation and judicial review, represent nations, nationalities and peoples rather than states), the regional states remain creations of the ‘imperial’ federal government whose political and fiscal control has continuously constrained their ability to function in any meaningfully autonomous way. This might very well be an endemic problem for federal systems that come into being through the disaggregative process, whereby a previously unitary system is disaggregated, as it were, for the purpose of federalism: more often than not, federalism becomes ‘a matter of the central government’s yielding a great deal of power to the substate units, often simply to facilitate the ability of ethnic contestants to live in separate compartments while purporting to inhabit a common central state’ (Horowitz 2007, 953). This seems to be true of the Ethiopian case, what with the one-party authoritarian regime built around the Ethiopian People’s Revolutionary Democratic Front (EPRDF) and its successor Prosperity Party (the EPRDF won 100% of the legislative seats in federal and regional parliaments in the 2015 elections), as well as Zenawism, which reflected he strong power wielded by former Prime Minister Meles Zenawi under whose government ethnic federalism was adopted, and later Prime Minister Abiy Ahmed. Yet the Ethiopian experiment with its provisions for strong regional states seemed to offer a solution. The declarations of states of emergency by the federal government in 2015, 2016 and 2021 that literally turned the country into a military state, however, deepened the authoritarian framework within which federalism has had to work. Perhaps, then, the inability of the regional states to counterbalance the dominance of the centre, which was one of the built-in expectations of ethnic federalism, due partly to structural disabilities (some of which have been highlighted above) and partly to the resurgent unification drive by coalition partners of the Prosperity Party who reject ‘divisive’ ethnic federalism, may have been a key driver for Tigray (and Oromo and Amhara) dissent and rebellion. The displacement from power at the centre of the Tigray People’s Liberation Front, which was the dominant force in the old EPRDF, may also have been another key propellant, as was the case with Afrikaners who, upon displacement from power in South Africa sought refuge in regional autonomy. The overbearing power of the central government is not the only pertinent issue in the travails of Ethiopia’s ethnic federalism, however. The recent insurgencies in particular have rekindled the age-old debate over the benefits or dangers of granting autonomy and self-determination rights to ‘self-contained’ ethnic nationalities, such as those in the regional states. On one side of the debate is the view that doses of autonomy, self-determination and self-governance are necessary for addressing problems of ownership and inclusivity in highly divided societies where equity and justice on the part of central governments are not assured. The clamour for resource control by groups that bear or produce commodities on which national economies depend, which has become widespread across Africa, for example, takes its cue from this. It is therefore not surprising that such demands are usually the first lines of defence by ethnic champions, insurgents and separatists in negotiations with state power-holders. In theory, at least, autonomy and self-determination are helpful for managing deeply divided societies, and this was expected to be one of the benefits of Ethiopia’s ethnic federalism. The opposing view considers free-will autonomy of the kind embodied in ethnic federation dangerous on at least two grounds. First, the implicit sense of ownership and independence of the regional state could harden ethnic identities and encourage feelings of exclusivity that lead to discrimination against so-called non-indigenes. This polarising tendency, which has been reported in several regional states in matters like access to land, education and employment, is similar to that of Nigeria where conflicts between indigenes and non-indigenes induced by a variant of ethnic federalism have aggravated national question contestations. These debates include demands for new (own) states. In 2019, the Sidama people voted overwhelmingly (98.5 %) for a separate state from the regional state of Southern Nations, Nationalities and Peoples. Second, autonomy and self-determination are likely to make the country more (permanently) divided and incentivise opposition, insurgency, separatism and secession, particularly when the nationalities – as regional states – perceive the central government to be encroaching upon, usurping or depriving them of their constitutionally guaranteed powers (such as the reduction of federal funding to Tigray in 2020). The rebellions of the Tigray People’s Liberation Front (TPLF),later branded Tigray Defence Force (TDF), Oromo Liberation Army (OLA), Afar Revolutionary Democratic Unity Front (ARDU), Benishangul People’s Liberation Movement (BPLM), Gambella People’s Liberation Army (GPLA), Global Kimant People’s Right and Justice Movement (GKPRJM), Kimant Democratic Party (KDP), Sidama National Liberation Front (SNLF) and Somali State Resistance (SSR), and the formation of the anti-Abiy alliance known as the United Front of Ethiopian Federalist and Confederalist Forces, have been largely attributed to these tendencies. This underlies the resurgent Ethiopia Tikdem movement that has gained traction with Abiy’s Prosperity Party, which seeks national unity through a coalition of ethnic political parties and movements, but which opposition forces see as intended to further strengthen the unitary-authoritarian framework and undermine the basis of ethnic federalism. The contradictions, tensions and troubles that Ethiopia is presently going through do not indicate that the ethnic federation model has failed. If anything, the system, which suits the historical, political, social and economic circumstances of a country that requires a balance between diversity and integration, has not been allowed to work as designed. The dissent and insurgencies are therefore to be seen as signposts that the federal system needs review, rebargaining and renegotiation, which may yet necessitate the adoption of new instrumentalities to make the regional states more effective and less exclusionary tiers of government,and the federal government more democratic and accountable. This is because federalism is a dynamic system, the viability, stability and ultimate success of which depends on the capacity of its managers to respond to changing political realities, forces and demands. The greatest dangers to federalism are not just the overbearing power of the federal government and authoritarian regimes but opportunistic elites who seek state capture at national and subnational levels for personal gain rather than the common good.